2019
DOI: 10.1055/s-0039-1688960
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Arthroplasty: Short-Term Complications and Risk Factors

Abstract: There is a paucity of literature regarding the short-term readmission, reoperation, and complication rates of patellofemoral arthroplasty (PFA). The purpose of this study is to determine the incidence and risk factors of 30-day postoperative complications in patients undergoing PFA. A retrospective cohort study of subjects who underwent PFA from 2010 to 2015 was performed using the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database. Perioperative outcomes and 30-day pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Another one of these studies demonstrated no significant correlation between race and post-operative VTE and only included elective pediatric orthopaedic procedures, thus the generalizability of these results to older populations is questionable 116 . One study examining short-term complications following patellofemoral arthroplasty had similar findings, however the time course chosen excludes any potential VTE events that could have occurred beyond thirty days 117 . Furthermore, a retrospective study conducted at a Level 1 trauma center found no difference in outcomes with respect to race for operatively treated tibia fractures 118 .…”
Section: - Is the Risk Of Vte Following Orthopaedic Procedures Relate...mentioning
confidence: 93%
See 1 more Smart Citation
“…Another one of these studies demonstrated no significant correlation between race and post-operative VTE and only included elective pediatric orthopaedic procedures, thus the generalizability of these results to older populations is questionable 116 . One study examining short-term complications following patellofemoral arthroplasty had similar findings, however the time course chosen excludes any potential VTE events that could have occurred beyond thirty days 117 . Furthermore, a retrospective study conducted at a Level 1 trauma center found no difference in outcomes with respect to race for operatively treated tibia fractures 118 .…”
Section: - Is the Risk Of Vte Following Orthopaedic Procedures Relate...mentioning
confidence: 93%
“…However, this is not a universal finding. A few studies have found no significant correlation between post-operative VTE and race [115][116][117][118][119] . Blum et al, found no association between VTE and African American race in analysis of a regional database 115 .…”
Section: -Are There Genetic Predisposing Factors For Vte?mentioning
confidence: 99%
“…Intraoperative, perioperative and postoperative complications were reported in each of the 20 articles 7 , 13 - 27 ( Table 2 ). From these, the researchers identified four articles that described patients affected by traumatic and periprosthetic fractures ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, bleeding is also responsible for a high percentage of revision surgeries (11.7%) within 30 days. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Patello-femoral arthroplasty is commonly used for symptomatic patello-femoral osteoarthritis or isolated osteochondral lesions without ligament instability ( Cotic et al, 2017 ; Jeong et al, 2020 ; Rezzadeh et al, 2020 ). The patient suffered from patello-femoral large osteochondral defects in our case, but patello-femoral arthroplasty could not achieve mechanical stability because of mass bone defects.…”
Section: Discussionmentioning
confidence: 99%